Legal Protection for Consumers Related to New Money Exchange Outside the Bank - Diah Wahyulina; Suryaningsih Suryaningsih; Galih Setyo Refangga (IHSA Institute, 2026)
This study examines the legal protection available to consumers engaging in new money exchange transactions conducted outside formal banking institutions. The practice of exchanging newly issued currency through informal or unauthorized parties often increases during festive seasons or special events, creating potential risks such as fraud, counterfeit money circulation, unfair pricing, and lack of accountability. This research analyzes the existing legal framework governing consumer protection, currency regulation, and financial supervision to determine the extent to which consumers are safeguarded in such transactions. Using a normative juridical approach, the study reviews relevant consumer protection laws, central bank regulations, and related statutory provisions. It evaluates the legal responsibilities of informal money exchange providers and identifies gaps in enforcement mechanisms (Ardelia & Herta, 2025). The findings indicate that while general consumer protection laws provide a foundational safeguard, specific regulatory oversight over informal currency exchange activities remains limited, resulting in legal uncertainty and weak preventive measures. The study concludes that stronger regulatory supervision, clearer sanctions, and increased public awareness are necessary to ensure effective legal protection for consumers. Enhanced coordination between financial authorities and law enforcement agencies is also essential to prevent abuse and protect consumer rights in non-bank currency exchange practices